Analisis Kesulitan Belajar Matematika Siswa Kelas VII SMPN 1 Tamansari dan Solusinya melalui Pendekatan Differentiated Instruction - Lisa Ervina (Lencana: Jurnal Inovasi Ilmu Pendidikan, 2025)
This study aims to analyze the learning difficulties in mathematics among 7th-grade students at SMPN 1 Tamansari and propose solutions through the Differentiated Instruction approach. A descriptive research method with a qualitative approach was employed to identify the factors contributing to students' learning difficulties. Data were collected through interviews, observations, and document analysis, then analyzed using data reduction, data presentation, and conclusion drawing techniques. The findings indicate that mathematics learning difficulties are influenced by weak conceptual understanding, low learning motivation, and a lack of varied teaching strategies. The implementation of Differentiated Instruction has been proven to improve students' learning outcomes by tailoring teaching methods to individual needs. This study recommends teacher training to enhance competence in applying Differentiated Instruction and developing innovative learning media to support successful mathematics instruction.